Taxonomic review of the lepida-group of Fannia R.-D. (Diptera: Fanniidae) - Zhang, Dong; Wang, Jing; Wang, Ming-Fu; Li, Kai (Zootaxa, 2011)
The Fannia lepida-group is reviewed. Fannia immutica Collin is recorded for the first time in China. A key to males of the four known species is provided. Fannia lepida (Wiedemann), F. grahami Chillcott, and F. immutica Collin are redescribed and the male terminalia illustrated. Fannia grahami remained unrecorded since its 1961 original description.